Data and code for "Revealing the free energy landscape of halide perovskites: Metastability and transition characters in CsPbBr3 and MAPbI3" - Fransson, Erik; Rahm, J. Magnus; Wiktor, Julia; Erhart, Paul (Chalmers University of Technology, 2023)
This record contains a neuroevolution potential (NEP) model (nep-MAPI-SCAN.txt ) for MAPbI3 used in the linked publication. The model can be used in conjunction with the GPUMD package. The calorine package provides a Python interface to GPUMD.
Several primitive structures in extended xyz format can be found in the *.xyz files. These structures have been relaxed using the NEP model included here. The demo-for-using-structures-and-model.py script illustrates how to access the structures and model.
Keywords: neuroevolution potential; GPUMD; halide perovskites; density functional theory; Physical Sciences; Fysik